Uji Daya Hambat Ekstrak Bawang Hutan (Eleutherine palmifolia (L.) merr) dari Matantimali Terhadap Pertumbuhan Jamur Candida albicans - Wahyuni, Sri; Nuryanti, Siti; Jura, Minarni Rama (Universitas Tadulako, 2016)
Forest onion is a plant that is widely used as a traditional medicine and natural antioxidants. The aim of this study is to determine the extract of the forest onion that can inhibit the growth of the fungus candida albicans and to compare the inhibitory of extract of the forest onion (eleutherine palmifolia (L.) merr) by using different solvents, namely ethanol and distilled water which is carried out by the method of pitting. Suspension of the fungus candida albicanswas obtained from Clinical Laboratory Palu, Central Sulawesi. The results of research obtained that the inhibition of extract of the forest onion on growth of the fungus candida albicanswith ethanol was greater than with distilled water, the percentace was 65.44% and 54.78% for each solvents. It can be concluded that extract of the forest onion has the inhibitory on the growth of the fungus candida albicans.